(untitled) (Interdisciplinary Studies Journal, 2026)
This study analyzes student participation and interdisciplinarity in Basic Education based on the reality of the Student Leadership Program in the municipality of João Pessoa – PB. The research adopts a qualitative, analytical-descriptive approach, grounded in a bibliographic review, documentary analysis of national and municipal legislation, and professional regulations, with emphasis on Law No. 13,935/2019 and the guidelines of the municipal school system of João Pessoa-PB. The results show that, although there have been normative and institutional advances recognizing interdisciplinarity and participation as principles of educational policy, structural, pedagogical, and organizational limitations persist, constraining their implementation in everyday school life. It is concluded that the consolidation of participatory and interdisciplinary practices requires pedagogical intentionality, articulation between curriculum, the political-pedagogical project, and school management, as well as objective working conditions that enable democratic, critical, and emancipatory education.